Question 1 of 5Determine which Equation Matches the Graph
Select the Correct Answer Below: Correct! Not Correct!
A
$$\frac{y^2}{4}-\frac{x^2}{16}=1$$
B
$$\frac{y^2}{16}+\frac{x^2}{4}=1$$
C
$$\frac{y^2}{16}-\frac{x^2}{4}=1$$
D
$$\frac{x^2}{16}-\frac{y^2}{4}=1$$
E
$$\frac{x^2}{2}-\frac{y^2}{4}=1$$
Question 2 of 5Determine which Equation Matches the Graph
Select the Correct Answer Below: Correct! Not Correct!
A
$$\frac{y^2}{25}-\frac{x^2}{9}=1$$
B
$$\frac{x^2}{25}+\frac{y^2}{9}=1$$
C
$$\frac{x^2}{25}-\frac{y^2}{9}=1$$
D
$$\frac{x^2}{5}-\frac{y^2}{3}=1$$
E
$$\frac{y^2}{\sqrt{5}}+\frac{x^2}{\sqrt{3}}=1$$
Question 3 of 5Determine which Equation Matches the Graph
Select the Correct Answer Below: Correct! Not Correct!
A
$$\frac{(y-2)^2}{9}-\frac{(x-1)^2}{16}=1$$ $$\frac{(y-2)^2}{9}\hspace{.25em}-$$$$\frac{(x-1)^2}{16}=1$$
B
$$\frac{(y-1)^2}{9}-\frac{(x-2)^2}{16}=1$$ $$\frac{(y-1)^2}{9}\hspace{.25em}-$$$$\frac{(x-2)^2}{16}=1$$
C
$$\frac{(y-2)^2}{9}+\frac{(x-1)^2}{16}=1$$ $$\frac{(y-2)^2}{9}\hspace{.25em}+$$$$\frac{(x-1)^2}{16}=1$$
D
$$\frac{(y-2)^2}{3}-\frac{(x-1)^2}{4}=1$$ $$\frac{(y-2)^2}{3}\hspace{.25em}-$$$$\frac{(x-1)^2}{4}=1$$
E
$$\frac{(x-2)^2}{3}+\frac{(y-1)^2}{4}=1$$ $$\frac{(x-2)^2}{3}\hspace{.25em}+$$$$\frac{(y-1)^2}{4}=1$$
Question 4 of 5Determine which Equation Matches the Graph
Select the Correct Answer Below: Correct! Not Correct!
A
$$\frac{(x-1)^2}{3}+\frac{y^2}{5}=1$$ $$\frac{(x-1)^2}{3}\hspace{.25em}+$$$$\frac{y^2}{5}=1$$
B
$$\frac{(x-1)^2}{9}-\frac{(y-1)^2}{25}=1$$ $$\frac{(x-1)^2}{9}\hspace{.25em}-$$$$\frac{(y-1)^2}{25}=1$$
C
$$\frac{(x+1)^2}{9}-\frac{y^2}{25}=1$$ $$\frac{(x+1)^2}{9}\hspace{.25em}-$$$$\frac{y^2}{25}=1$$
D
$$\frac{(x+1)^2}{\sqrt{3}}+\frac{(y-1)^2}{\sqrt{5}}=1$$ $$\frac{(x+1)^2}{\sqrt{3}}\hspace{.25em}+$$$$\frac{(y-1)^2}{\sqrt{5}}=1$$
E
$$\frac{(y+1)^2}{9}-\frac{x^2}{25}=1$$ $$\frac{(y+1)^2}{9}\hspace{.25em}-$$$$\frac{x^2}{25}=1$$
Question 5 of 5Determine which Equation Matches the Graph
Select the Correct Answer Below: Correct! Not Correct!
A
$$(x-2)^2-(y-1)^2=1$$ $$(x-2)^2\hspace{.25em}-$$$$(y-1)^2=1$$
B
$$(x-1)^2-(y-2)^2=1$$ $$(x-1)^2\hspace{.25em}-$$$$(y-2)^2=1$$
C
$$\frac{(x-1)^2}{\sqrt{2}}-\frac{(y-2)^2}{\sqrt{2}}=1$$ $$\frac{(x-1)^2}{\sqrt{2}}\hspace{.25em}-$$$$\frac{(y-2)^2}{\sqrt{2}}=1$$
D
$$(x+1)^2-(y+2)^2=1$$ $$(x+1)^2\hspace{.25em}-$$$$(y+2)^2=1$$
E
$$\frac{(x+1)^2}{\sqrt{2}}-\frac{(y-2)^2}{\sqrt{2}}=1$$ $$\frac{(x+1)^2}{\sqrt{2}}\hspace{.25em}-$$$$\frac{(y-2)^2}{\sqrt{2}}=1$$

Great Job! You Passed!

Better Luck Next Time...

Restart Quiz ↻
Review Lesson ↻
Next Lesson »